An experimental study on the long-term and short-term effects of PRP treatment on the endometrium and ovaries - Budak, Özcan; Toprak, Veysel; Türkler, Can (Journal of Surgery and Medicine, 2020)
Aim: It has been reported that ovaries have stem cells, and they can be used in the treatment of patients with low ovarian reserves by maturing them through some growth factors. PRP, a new therapy, has many bioactive compounds including growth factors. This study aimed to investigate the long and short-term biochemical and histopathological effects of platelet-rich plasma (PRP) treatments on the lining of the uterus and the ovaries in rats. Methods: Female rats (n = 21) were randomly divided into 3 groups: A sham group, a short-term PRP group and a long-term PRP group. At the end of the study, anti-Mullerian hormone (AMH) and follicle-stimulating hormone (FSH) levels were examined in blood samples obtained from the intracardiac area, and the ovaries and uterus of the rats were examined to determine the histopathological and immunohistochemical findings. Results: The results of this study demonstrated that, in the blood samples of the rats, the AMH levels increased and FSH levels decreased in the short-term PRP group (P<0.05). When the uteri and ovaries of the rats were examined histopathologically, positive and beneficial effects of the PRP therapy were found in the short-term PRP group. However, considering the long-term results, the positive effects of PRP decrease as time goes on. Conclusion: This study showed that PRP application delivers beneficial effects to the uterus and ovaries in female rats in the short term.